Answer:
D. y - 5 =3(x + 1)
Explanation:
Given equation of line:
![y = -(1)/(3)x-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i1isr1tvqcu46lwbgpnegq7gjd7eq2t7rl.png)
Comparing it with the standard form of equation of line
y=mx+b
m = -1/3
Let m1 be the slope of line perpendicular to the given line.
We know that the product of slopes of two perpendicular lines is -1.
![m*m_1 = -1\\-(1)/(3) * m_1 = -1\\ m_1 = -1 * -(3)/(1)\\ m_1 = 3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kfbdg2ryo6oksz6nqmki78bacovg0ittgk.png)
The equation of line in point slope form is:
![y-y_1 = m(x-x_1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/93b26olc127sd9hs43a8jucrvrl5pg0lo9.png)
where x_1 and y_1 is the point from which the line passes.
So, putting the values of slope and point,
![y-5 = 3[x-(-1)]\\y-5=3(x+1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fsllpy4hdjerixhl45lfipm3n48oy2ps76.png)
Option D is correct ..